Solubility of ligated gold nanoparticles at room temperature in various hydrocarbon solvents - Lohman, Brandon (Kansas State University, 2009)
Gold Nanoparticles (AuNP) 5nm in diameter, ligated with n-dodecanethiol, were dissolved in various hydrocarbon solvents including normal alkanes from n-hexane to n-hexadecane as well as two aromatics, toluene and para-xylene. These solutions were centrifuged at room temperature under 12000g acceleration for one hour to separate larger clusters from AuNP monomers dissolved in the supernatants. UV-Vis absorbance data were taken on the supernatants and were then converted to concentrations in moles of Au atoms/L. These concentrations correspond to the saturated concentration of dissolved AuNP monomers in equilibrium with a precipitate at room temperature. For the alkanes, we discovered a non-monotonic functionality of saturated concentration vs. solvent chain length with a maximum corresponding to n-dodecane. This agreed with predictions made of the ligands’ interactions with the solvents based on comparisons of solubility parameters where the n-dodecanethiol ligands were approximated as n-dodecane. The concentrations of AuNPs when dissolved in the aromatics did not follow the trend predicted by solubility parameters.
Keywords: Nanoparticle; Solubility; Hydrocarbon; Solvent; Gold; Alkane; Chemistry, Physical (0494); Physics, Condensed Matter (0611)